RUANG PUBLIK KOTA DAN POLA KOMUNIKASI WARGANYA - Herutomo, Christoperus (Acta Diurna: Jurnal Ilmu Komunikasi, 2017)
Arrangement of urban public space that takes into account social, cultural, economic and characteristic aspects of urban citizens will affect the pattern of urban citizens communication that is anonymity. The anonymity nature of the citizens of this city is due to the very heterogin city residents consisting of ethnic background, religion, socioeconomic status and interests. The anonymity of the townspeople causes a tendency for citizens to communicate with people or groups with similar backgrounds and interests. Communication citizens who have the background and interests of the same this will lead to the pattern of communication that is the primary of personal communication, informal and expressive. This pattern of primary communication can be at the individual level such as family communication as well as group level such as communication in organizations that use city public space.